An analysis pipeline for FAIRE-seq data (2012)
Sites across eukaryotic genomes, where disturbance or eviction of nucleosomes from chromatin takes effect, are highly correlated with the presence of active regulatory elements. Formaldehyde-assisted isolation of regulatory elements coupled with high-throughput sequencing (FAIRE-seq) has been proven successful insolating those genomic regions. FAIRE-seq identified regions agree with results obtained using nuclease hypersensitivity or chromatin immunoprecipitation. Furthermore, FAIRE-seq increases the reproducibility of experiments because it is independent on the use of enzymes and antibodies. However, several computational analyses are required for the interpretation on genome-wide results. Also, FAIRE-seq represents challenges related with its signal characteristics.